A Field Study of the Acoustical Insulation of Residential Construction - Bechrakis, Nikolas (My University, 1981)
The angle of incidence is a major variable for calculating transmission loss from field data [A.S.T.M 336-77]. This suggests that the acoustical insulation of residential construction may vary with the relative location of the flight paths and the housing. Alternatively, the Central Mortgage and Housing Corporation assumes in its guideline that the number of reflected paths in normal residential areas is so great as to override any such effect.
The first objective of this study is to investigate the effect of the angle of incidence on the acoustical insulation in residential construction. The second objective is to compare the acoustical insulation as calculated from field transmission loss data with the one estimated in the C.M.H.C. guideline.
Field transmission loss data were collected for each one-third octave band for 30 rooms in the Toronto airport area. The first objective is studied using data from rooms affected by aircraft noise, where the flight path is perpendicular to the place defined by the element of interest, as well as from rooms affected by road traffic noise. The variation of the acoustical insulation over time is studied. The results suggest that there is a noticeable effect of the angle of incidence for the houses exposed to aircraft noise. The second objective is studied using data from rooms affected by aircraft noise. The acoustical insulation estimated by C.M.H.C. is found to be lower than the one calculated from field transmission loss data.
Keywords: Civil Engineering; Civil Engineering